Calibration of the comet assay using ionising radiation - Brunborg, Gunnar; Eide, Dag M; Graupner, Anne; Gutzkow, Kristine; Shaposhnikov, Sergey; Kruszewski, Marcin; Sirota, Nikolai; Jones, George D D; Koppen, Gudrun; Vanhavere, Filip; Møller, Peter; Stetina, Rudolf; et al. (Mutation research. Genetic toxicology and environmental mutagenesis, 2023)
Several trials have attempted to identify sources of inter-laboratory variability in comet assay results, aiming at achieving more equal responses. Ionising radiation induces a defined level of DNA single-strand breaks (per dose/base pairs) and is used as a reference when comparing comet results but relies on accurately determined radiation doses. In this ring test we studied the significance of dose calibrations and comet assay protocol differences, with the object of identifying causes of variability and how to deal with them. Eight participating laboratories, using either x-ray or gamma radiation units, measured dose rates using alanine pellet dosimeters that were subsequently sent to a specialised laboratory for analysis. We found substantial deviations between calibrated and nominal (uncalibrated) dose rates, with up to 46% difference comparing highest and lowest values. Three additional dosimetry systems were employed in some laboratories: thermoluminescence detectors and two aqueous chemical dosimeters. Fricke's and Benzoic Acid dosimetry solutions gave reliable quantitative dose estimations using local equipment. Mononuclear cells from fresh human blood or mammalian cell lines were irradiated locally with calibrated (alanine) radiation doses and analysed for DNA damage using a standardised comet assay protocol and a lab-specific protocol. The dose response of eight laboratories, calculated against calibrated radiation doses, was linear with slope variance CV= 29% with the lab-specific protocol, reduced to CV= 16% with the standard protocol. Variation between laboratories indicate post-irradiation repair differences. Intra-laboratory variation was very low judging from the dose response of 8 donors (CV=4%). Electrophoresis conditions were different in the lab-specific protocols explaining some dose response variations which were reduced by systematic corrections for electrophoresis conditions. The study shows that comet assay data obtained in different laboratories can be compared quantitatively using calibrated radiation doses and that systematic corrections for electrophoresis conditions are useful.
Keywords: poškození DNA; Radiation, Ionizing; Ring-trial; Mammals; Comet Assay; DNA Damage; ionizující záření; kalibrace; Gamma Rays; savci; Dose-Response Relationship, Radiation; Animals; lidé; Humans; zvířata; kometový test; Standardisation; Radiation; vztah dávky záření a odpovědi; záření gama; Calibration; Comet assay